Air pollution, weather variations and primary spontaneous pneumothorax - Bertolaccini, Luca; Alemanno, Laura; Rocco, Gaetano; Cassardo, Claudio (Journal of Thoracic Disease; Vol 2, No 1 (March 11, 2010): Journal of Thoracic Disease, 2011)
No abstract.